2017
DOI: 10.1107/s1600576717003831
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron Bragg diffraction imaging characterization of synthetic diamond crystals for optical and electronic power device applications

Abstract: Bragg diffraction imaging enables the quality of synthetic single-crystal diamond substrates and their overgrown, mostly doped, diamond layers to be characterized. This is very important for improving diamond-based devices produced for X-ray optics and power electronics applications. The usual first step for this characterization is white-beam X-ray diffraction topography, which is a simple and fast method to identify the extended defects (dislocations, growth sectors, boundaries, stacking faults, overall curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…This phenomenon is related to the growth of sample 2. X‐ray white topography is a method used to examine the microstructure defects of crystal material, and it is widely used in the study of the integrity of crystal material . Figure a shows an X‐ray white morphology image of HPHT type Ib seed substrate, showing the defects of the seed substrate and their distribution.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is related to the growth of sample 2. X‐ray white topography is a method used to examine the microstructure defects of crystal material, and it is widely used in the study of the integrity of crystal material . Figure a shows an X‐ray white morphology image of HPHT type Ib seed substrate, showing the defects of the seed substrate and their distribution.…”
Section: Resultsmentioning
confidence: 99%
“…However, this difficulty did not occur on HP/HT type IIa substrates with a few ppm of nitrogen impurities. The impurity amount of “general grade” single‐crystal CVD diamond (Element Six Ltd.) is unknown, but it is presumably equal to or smaller than that of HP/HT type IIa: it is described elsewhere in the literature as less than 5 ppm in “optical grade” elsewhere in the literature …”
Section: Resultsmentioning
confidence: 99%
“…Regarding crystallinity, an earlier study reported synchrotron radiation topography for single‐crystal CVD (low‐grade) (Element Six Ltd.), HP/HT type Ib single‐crystal (Sumitomo Electric Industries, Ltd.), and HP/HT type IIa single‐crystal diamond (Element Six Ltd.). Although produced by different manufacturers, HP/HT type IIa crystal shows the least dislocation.…”
Section: Resultsmentioning
confidence: 99%
“…The rocking curves of the two types of seed substrates and CVD layers grown on each were measured by a Bruker D8 DISCOVER X-ray high-resolution diffractometer using a monochromized Cu-Kα1 X-ray source with a Ge (220) four-crystal monochromator. X-ray topography is a powerful tool for studying extended defects such as dislocations and stacking faults [23,24]. X-ray topography was performed on two types of seed substrates and the samples grown on each.…”
Section: Methodsmentioning
confidence: 99%
“…(c, d) X-ray topography images of as-grown CVD seed substrate. The X-ray rocking curve is very sensitive to dislocations and other defects in the crystal, and the quality of the crystal can be judged according to the FWHM of rocking curve [23]. When the dislocation density is high (10 4 -10 7 cm -2 ), the dislocation density (Nd) of the sample can be calculated from the FWHM of rocking curve, which was calculated by the formula [33]: Nd=(△θ1/2) 2 /9b 2 , where △θ1/2 and b are the real FWHM of the double crystal diffraction of a specimen crystal and Burgers vector length, respectively.…”
Section: Quality Analysis Of the Cvd Layersmentioning
confidence: 99%